A case of deletion 14(q22.1–>q22.3) associated with anophthalmia and pituitary abnormalities. Issue 3 (March 1993) - Elliott, J; Maltby, E L; Reynolds, B
Abstract : An interstitial deletion of the region q22.1–>q22.3 of chromosome 14 is described in a child with bilateral anophthalmia, dysmorphic features including micrognathia, small tongue, and high arched palate, developmental and growth retardation, undescended testes with a micropenis, and hypothyroidism. Interstitial deletions of the long arm of chromosome 14 are extremely rare, but this case seems to confirm that the region q22 is specifically concerned with pituitary and eye development.